Staatkundige brieven. Serie 1926 (Tjeenk Willink, 1926)
Dl. 1. No 3, 7 Januari 1926. Dl. 2-4. Kritieke tijden (Textueele overn. vrij). No 1. 17 November 1926. No 2. 1 December 1926. No 3. 18 December 1926.